The Effect of Ethics and Service Quality of Health Workers on Patients Satisfaction at dr. Soepraoen Hospitals Malang - Arief Efendi; Anis Ansyori; Fita Rusdian Ikawati; Silvia Intan Wardani (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2021)
Patient satisfaction cannot be separated from the code of ethics and quality service carried out by medical personnel. This study aims to determine the effect of Ethics and Service Quality of Health Workers on Patients Satisfaction at dr. Soepraoen Hospitals Malang. The research method used is descriptive analytic research. With a cross sectional study design. The population in this study were 100 people. The result of this study is there is a positive and significant effect of ethics health workers partially on patient satisfaction, there is a positive and partially significant effect of partially Service Quality on patient satisfaction, there is a simultaneous positive and significant effect of ethics health workers and Service Quality on patient satisfaction.